1. The problem statement, all variables and given/known data H(z)=1/(1-2/3*z-1) h(n)=? 2. Relevant equations I tried to use the residue method to solve this problem but it doesnt give me the good result and i am not sure if i dont know how to use the method or this problem cant be solved using this method. Also, its pretty obvious that the result is h(n)=(2/3)n because it looks like a geometric progression 3. The attempt at a solution I used the formula of residue method. h(n)=residue(H(z)*zn-1) when z=2/3 The result is 3*(2/3)n Its this result wrong because when we calculate Z transform of (2/3)n which is (1-(2/3)n*z-n )/(1-(2/3)*z-1) we ignore (2/3)n because is 0 when n=infinity?